F20. Focal status epilepticus in a patient with stroke like migraine attacks after radiation therapy (SMART) syndrome. (May 2018) - Manacheril, Rinu; Khan, Fawad A.; Steven, Andrew; Menon, Uma; Billeaud, Neil; Sabharwal, Vivek; Ramsay, Richard E.
Abstract : Introduction: Stroke like migraine attacks after radiation therapy (SMART) syndrome is a rare and under-recognized delayed complication of brain irradiation. It is characterized by cortical thickening with associated cortical gadolinium enhancement on magnetic resonance imaging (MRI) and with migraine headaches, typically reversible stroke like symptoms and focal seizures. Focal status epilepticus (SE) is a rare phenomenon associated with SMART syndrome. Methods: We present a case of SMART syndrome with focal seizures and SE. We also reviewed the literature on SMART and SE. Results: A 46 year old male with history of human immunodeficiency virus, hypertension, diabetes mellitus II, brain lymphoma (treated with brain irradiation) presented with a two week history of right parietal headache with involuntary left leg movement and left hemi-neglect on exam. MRI showed evidence of cortical and subcortical T2/FLAIR hyperintensity with cortical and leptomeningeal enhancement involving the right parietal region. Serum paraneoplastic and infectious workup was negative. Cerebrospinal fluid (CSF) analysis was remarkable for albuminocytologic dissociation. CSF cytology was negative for malignancy. Electroencephalogram (EEG) sowed slowing over the right parasagittal area without evidence of epileptiform activity. Symptom resolution was achieved with intravenous valproic acid 500 mg twice daily (BID). He remained asymptomatic until readmission 9 months later for a 2 week history of right parietal headache along with altered sensory perception of the left arm and leg in space and left sensory extinction. CSF analysis and brain MRI findings were unchanged. Brain biopsy was negative for malignancy. EEG showed multiple electrographic seizures in the right posterior region. The SE was treated with brivaracetam 100 mg BID, valproic acid 500 mg BID and vigabatrin 1500 mg BID and later with topamax 200 mg BID, levetiracetam 1500 mg BID and lacosamide 100 mg BID. Seizure freedom was achieved at 3 weeks. Patient was discharged home on levetiracetam 500 mg BID and lacosamide 100 mg BID. Patient was readmitted a week later for agitation prompting discontinuation of both medications with initiation of eslicarbazepine 1200 mg daily was initiated with no recurrence of symptoms or side effects. At a 4 week follow up he remained asymptomatic. We reviewed the literature and identified five previously reported cases of SE associated with SMART syndrome. Conclusion: Seizures are not uncommon in patients with SMART syndrome likely secondary to underlying cortical irritability. Focal SE is rare and can be seen with SMART syndrome. Our report emphasizes the need to recognize SMART syndrome in a patient with headache and focal SE with a history of brain irradiation.